Análisis y desarrollo de estrategias para la prevención del uso de la Ingeniería Social en la sociedad de la información (2013)
Social Engineering can be defined as those strategies and techniques used to obtain information from people. In order to understand how social engineering affects a system and even how it affects ourselves, there are two scenarios: the first is where the social engineer interacts with a potential victim in different ways (e-mail, phone calls and short message services), using persuasion, fraud and threats in some cases, to obtain inside information of a system he wants to attack but using people as a means to do it, the second one is where the social engineer thinks of people as their main objective using the same forms and techniques mentioned above but he is not looking information of them, instead of that what drives him is the money using their skills to enrich themselves at the expense of others.